Pengetahuan Investasi Dan Motivasi Dalam Meningkatkan Minat Mahasiswa Prodi Manajemen Berinvestasi Di Pasar Modal Melalui Galeri Investasi Universitas Muhammadiyah Makassar - Alvy Zhaqila; Andi Rustam; Muhaimin (Lembaga Pengembangan Kinerja Dosen, 2025)
The aim of this studys is to determine the effect of investment knowledge and motivation on students interest in investing in the capital market through the Investment Gallery of Muhammadiyah University of Makassar. The sample of the study consisted of 76 respondents from the 2021 student. This study uses a quantitative research method. The data source is primary data collected through questionnaires. The research instrument used a Likert scale method. Based on the results of the research using SPSS V 25, it was found that investment knowledge and motivation have a positive influence on students interest in investing in the capital market. The higher the investment knowledge and motivation, the greater the stidents interest in investing in the capital market